2023
DOI: 10.3390/pharmaceutics15020709
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and In Vitro Characterization of Telmisartan Loaded Sodium Alginate Beads and Its In Vivo Efficacy Investigation in Hypertensive Induced Animal Model

Abstract: Background: Antihypertensive drug telmisartan (TEL) belongs to BCS class II, which is characterized by low water solubility and, consequently, low oral bioavailability. Gastroretentive systems may overcome the problems associated with low solubility of TEL and incomplete absorption by localizing the drug release in the stomach. The purpose of this study was to prepare TEL-loaded, oil-entrapped, floating alginate beads with the intent of enhancing the oral bioavailability of TEL for the treatment of hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…The objective of the study, which was to enhance the oral bioavailability of telmisartan by creating oil-entrapped telmisartan beads, was successfully proved by an in vivo study that confirmed an extended anti-hypertensive activity of the API. In vitro studies confirmed the in vivo results as the formulation proved to have a high entrapment efficiency percentage and remained buoyant for 7 h while showing an extended release over 12 h in a simulated gastric fluid [ 58 ]. Microporous systems are another category of multiple-unit FDDSs, obtained through the encapsulation of a drug reservoir inside a microporous compartment, presenting pores along the walls.…”
Section: Grdds Classificationmentioning
confidence: 67%
“…The objective of the study, which was to enhance the oral bioavailability of telmisartan by creating oil-entrapped telmisartan beads, was successfully proved by an in vivo study that confirmed an extended anti-hypertensive activity of the API. In vitro studies confirmed the in vivo results as the formulation proved to have a high entrapment efficiency percentage and remained buoyant for 7 h while showing an extended release over 12 h in a simulated gastric fluid [ 58 ]. Microporous systems are another category of multiple-unit FDDSs, obtained through the encapsulation of a drug reservoir inside a microporous compartment, presenting pores along the walls.…”
Section: Grdds Classificationmentioning
confidence: 67%
“…If we can dissolve solubilized nanoparticles alongside the SA matrix, the polymer erosion in the gastrointestinal tract will lead to an extended-release profile of the encapsulated drugs. With the coacervation method, we add the SA solution dropwise to the calcium ion solution, and small beads will be formed; these can be freeze-dried, providing long-term stability and excellent swelling ability, with systems that float on top of gastric juice [17,18] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…If we can dissolve solubilized nanoparticles alongside the SA matrix, the polymer erosion in the gastrointestinal tract will lead to an extended-release profile of the encapsulated drugs. With the coacervation method, we add the SA solution dropwise to the calcium ion solution, and small beads will be formed; these can be freeze-dried, providing long-term stability and excellent swelling ability, with systems that float on top of gastric juice [17,18] (Figure 1). This methodology provides physical encapsulation of the drugs and the nanocarrier system; however, there are alternatives where chemical conjugation would occur between This methodology provides physical encapsulation of the drugs and the nanocarrier system; however, there are alternatives where chemical conjugation would occur between the nanocarrier-forming polymer, lipid, etc., and the sodium alginate biopolymer.…”
Section: Introductionmentioning
confidence: 99%